Exploiting Intel Optane SSD for Microsoft SQL Server - Wu, Kan; Arpaci-Dusseau, Andrea; Arpaci-Dusseau, Remzi; Sen, Rathijit; Park, Kwanghyun (DaMoN 2019, 2019)
New NVM-based devices provide unparalleled performance (i.e., significantly reduced latency) than Flash-based SSDs. In this paper, we look into exploiting an NVM-based block device – the Intel Optane SSD – as a caching layer for Microsoft SQL Server. We reveal that naive usage of Optane SSD can result in up to 23% higher query response time than Flash SSD. We explain the issues of simple caching by analyzing the I/O characteristics of Intel Optane SSD. To exploit Optane SSD as a caching layer, we propose an Optane SSD-aware caching strategy including an optimized cache replacement policy and a cache access filter.